2012
DOI: 10.7547/1020054
|View full text |Cite
|
Sign up to set email alerts
|

Podiatric Health Needs of Homeless Populations as a Public Health Concern

Abstract: The small number of studies published so far all emphasize the major public health need for podiatric care among homeless populations. More studies are needed to help address this important public health concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…recently published a study that found foot health to be an often overlooked health problem and highlighted the health importance of foot care in homeless populations, particularly in preventing limb-threatening pathologies. [27] Thus, the foot problems reported in our study further highlight the increased risk that the homeless population has in developing lower-extremity pathologies. Aside from deformities or peripheral neuropathy, the acquisition of adequate shoes and socks can potentially have a major impact on this often-concealed problem.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…recently published a study that found foot health to be an often overlooked health problem and highlighted the health importance of foot care in homeless populations, particularly in preventing limb-threatening pathologies. [27] Thus, the foot problems reported in our study further highlight the increased risk that the homeless population has in developing lower-extremity pathologies. Aside from deformities or peripheral neuropathy, the acquisition of adequate shoes and socks can potentially have a major impact on this often-concealed problem.…”
Section: Discussionsupporting
confidence: 52%
“…Foot problems are an often over-looked condition that is not reported by most studies on the homeless population; nonetheless, it is a problem that has been observed. [2227] Chen et al . recently published a study that found foot health to be an often overlooked health problem and highlighted the health importance of foot care in homeless populations, particularly in preventing limb-threatening pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…[3], [5], [6] Given the prevalence and significant morbidity of foot health concerns, these findings have important service provision and public health implications. Homeless individuals often believe that healthy feet are important and are interested in receiving information about how to maintain adequate foot hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…[3], [5], [6] Despite the prevalence of foot problems in this population, there are significant gaps between foot health needs and research studies to address these needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation